Privacy Perceptions Transformation in Cairo’s Home Designs - A Case Study: Gated Communities - Esmat, Yasmine (AUC Knowledge Fountain, 2023)
The infrastructure of gated communities in Egypt’s New Cairo and 6th of October cities have become the new normal. The streets bordered by fences, walls, and the occasional gate, formed when two or more gated communities face each other, dominate the urban landscape today (Kostenwein, 2021). Nowadays, it is highly common to see billboards advertising new gated communities everywhere on the roads and bridges. Gated communities offer various privileges, and one of them is privacy. Taking Cairo city with its several gated communities as a case study, the research focuses on the transformation of privacy perception for Cairo’s home designs and examine how it is related to the aspiration of living in the current modern era. Target users are residents of an upper middle/upper social class, who moved from an apartment in the middle of the city to those gated communities in the outskirts of Cairo. How people define and value privacy is an ever-changing perception due to several factors such as the infiltration of capitalism, the effect of regulations and practices, and the desire to live in this modern lifestyle. This transformation of privacy is also reflected in the architecture of the new-gated communities in New Cairo, which includes certain constellations in relation to specific discourses, materials, forms, behaviors, and settings. All this information led to comprehending how privacy has transformed in the Egyptian society and understand the dimensions of privacy in gated communities in the outskirts of central Cairo. At the end, the research aims to tackle how people’s perception regarding privacy may have changed or has been adapted to this new western model of living in the hope of moving to a place which is less crowded, trendy, with high quality of living, and a modern look. It proceeds with the core question “Did people’s privacy perception change in relation to moving to their current home for the aspiration to be modern? How and why? “A mixed method approach was adopted across four gated communities: Palm Hills, Sodic, Mountain View and New Giza. A digital survey (n = 208) was designed to gather quantitative data regarding the “what” and “how” of privacy perceptions and elements, then it was followed by in-depth semi-structured interviews (n = 31) to collect qualitative data concerning the “why’s”. Questions in the survey and the interviews were driven by three main themes: 1) factors affecting residents’ privacy perceptions in their previous home vs. their current home, 2) behavioral implications of residents in both homes and 3) Needs and expectations of home privacy. Key questions addressed the reasons for choosing the gated community and the unit type of the interlocuter, privacy importance, privacy satisfaction in both homes, privacy strategies used to adjust the privacy levels if it was lacking and lastly privacy concepts in relation to architectural modernity. Results revealed how privacy was perceived in both homes, how social and physical factors affected that change of perception and what people needed to feel privacy. Concluding themes showed that developers are selling a dream home with a void idea of privacy due to economic factors affecting the physical design of privacy in home designs. This caused a matter of prioritization, the creation of new dichotomies and new tolerance to privacy, leading to a change in privacy perceptions. At the end, this adjusting paradigm has produced different vocabularies, understandings, and boundaries that can be used as an entry point by designers and architects in their designs and planning of new gated communities taking stock of how the potential residents constitute privacy.